Ultimate bearing capacity of cement columns treated peat soil using physical model - Loi, Shi Jun (2016)
Peat soil is classified as soft soil and problematic soil due to its natural properties of high compressibility, low shear strength and high initial water content. Cement column method is commonly used to stabilise the soil by changing the properties of soil. This research aimed to study the unconfined compressive shear strength and ultimate vertical bearing capacity of stabilized tropical peat of East Coast of Penisular Malaysia by a group of deep mixed cement column using a series of physical model test. To study the strength behaviour of peat soil with or without the cement stabilization, a series of physical laboratory models were conducted with different factor of variables, the number of cement column, proportion of binders (Ordinary Portland Cement) and pozzolanic materials (Palm Oil Fuel Ash). In this research, a total of 9 physical models of peat soil including one without the stabilized cement column as the control sample were conducted. A group of 4 and 6 cement columns with 25 mm diameter and 200 mm in length was considered. All the sample was cured for 28 days after the mixing of cement column. After the curing process, a series of axial loads were applied uniformly on the pre-fabricated steel plate footing from the top of the cement column in order study the ultimate bearing capacity of the stabilised soil. The change in strength of the samples was evaluated using Unconfined Compressive Strength (UCS) test. Based on the results from the tests, the highest recorded ultimate bearing capacity is in Model 6 with 6 cement columns with the area improvement ratios of 18.83 %. This research found that the sample with 300kg/m3 OPC has the highest UCS value of 106.88 kPa. However, the cement columns mixed with OPC and POFA aided in improving the strength and the ultimate bearing capacity of the peat soil.